Masculinization on tilapia (Oreochromis sp.) by natural hormone steroid agent from bee resin through artificial diet - Dinar Tri Soelistyowati; Agus Oman Sudrajat; Harton Arfah (Jurnal Akuakultur Indonesia)
Masculinization on tilapia ( Oreochromis sp.) has been done with approach of natural hormone steroid agent  from bee resin  through artificial diet before sexual differentiation. This research aim to increase male sex ratio and production performance. Treatment of bee resin dose is 0.6; 1.2; 1.8; 2.4; 3.0 feed ml/kg compared to Control (0 ml/kg diet) were given  during 28 days at larva age 7 day in aquarium, then transferred to the farm ground until age 12 weeks. Average of masculine phenotype percentage increased significantly (P